Design kadeřnického křesla - Nečasová, Barbora (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2008)
Diplomová práce se zaměřuje na návrh designu kadeřnického křesla. Inovací je nové uspořádání interiéru, jehož nepostradatelnou součástí je mycí komponent. Nosnou myšlenkou celého projektu je návrh kadeřnického křesla, které nahrazuje ostatní používaná sedadla v interiéru. Všechny činnosti spojené s úpravou vlasů jsou prováděny na jednom sedadle, které může být přisunuto k mycímu komponentu. Sklopením zádové opěrky a natočením mycí mísy je možné zákazníkovi umýt hlavu nebo provést jiný úkon vyžadující umyvadlo. Řešení přináší několik výhod, především méně sedadel v kadeřnictví a variabilitu interiéru. Další kladnou stránkou je ekonomicky výhodnější mycí komponent, který slouží více sedadlům. Inovací je také vzhledové a tvarové propojení dvou základních komponentů – mycí mísy a kadeřnického křesla.

This thesis aims to design a modern innovative hairdresser chair. The main innovation of the proposal is seen in the new interior arrangement with a washing component as a central point. The main idea of the whole work is to design such a hairdresser chair that would supersede all other chairs normally used in hairdressing salons. All activities concerned with the hair care (washing, trimming, colouring etc.) would be done on a sole chair that would be in the case of need placed to the washing component. By reclining the chair backrest and turning the washing component a client’s hair could be easily washed (or other functions that need water tap could be done). There are several advantages within this proposal. Primarily it offers fewer chairs in hair dressing salon as well as a more variable interior. Another positive feature is that the washing component can be used more economically when it serves to more seats. Finally, the visual aspect and shape interconnection of two basic components - washing basin and hairdresser’s chair - are innovative.
Design of armchair for hairdressing
Keywords: kadeřnické křeslo; kadeřnické umyvadlo; mycí komponent; design; hairdreser chair; washing component; wash bowl; design